The Effect of Long Service Life on the Accuracy of Dentaport ZX Electronic Apex Locator - parirokh, masoud; Manochehrifar, Hamed; Shahravan, Arash; Hosseini, Hamid Reza; Samanipoor, Siamak (Iranian Endodontic Journal, 2022)
Introduction: Electronic apex locators are among the most acceptable instruments for determining root canal length. The present study aimed to evaluate the effect of long service life on the accuracy of the Dentaport Root ZX (DP ZX) electronic apex locator (EAL). Materials and Methods: In this study, fifty single-rooted freshly extracted human teeth were used. After determining the root canal length with a K-file and a dental operative microscope, the canals were measured with four separate DP ZX apex locators (two with more than 6 years of life service while two others had less than 6 years of life service). Data were analyzed by repeated ANOVA measurement. Results: No significant difference was found between the EALs with different years of life services (P=0.62). All EALs could determine root canal length with high accuracy of more than 94%. Conclusion: Based on the results of this in vitro study, the long service life had no significant impact on the accuracy of DP ZX EALs in terms of root canal length determination.